Daily exercise training protects against albuminuria and angiotensin converting enzyme 2 (ACE2) shedding in db/db diabetic mice - Somineni, Hari K. (2014)
Angiotensin II (Ang II) is involved in induction and progression of renal damage in diabetes. Angiotensin converting enzyme 2 (ACE2) is highly expressed in the kidney and has been shown to be renoprotective by degrading Ang II to Ang-(1–7). Disintegrin and Metalloproteinase (ADAM) 17 mediated shedding of renal ACE2 contribute to diabetic nephropathy pathogenesis. Lifestyle modification and metformin are recommended as initial therapies for most patients with type 2 diabetes. The aim of the study was to investigate whether exercise training and/or metformin improve glucose homeostasis, albuminuria and downregulate renal ADAM17 and ACE2 shedding in db/db mice. Seven wk old normal and db/db mice were subjected either to sedentary or exercise training with and without metformin (150 mg/kg/day) for 10 wks. Exercise training significantly lowered blood glucose, urinary albumin and ACE2 excretion in db/db mice. ADAM17 and ACE2 proteins were co-localized in cortical tubules of the kidney, suggesting a possible interaction. Metformin treatment was effective in lowering hyperglycemia only during the first 2 weeks of treatment. Increased renal ADAM17 in 17 wk old db/db mice was corrected by physical exercise but not metformin. In addition, exercise training reduced plasma triglycerides and enhanced insulin levels of db/db mice. In conclusion, exercise training alone and in combination with metformin prevented shedding of renal ACE2 by decreasing ADAM17 protein. Urinary ACE2 could serve as a prognostic tool in the progression of kidney damage and its attenuation by exercise may partially contribute to its renal protection.